Inhibition of osteoclastogenesis by opsonized Porphyromonas gingivalis. Issue 4 (5th February 2019) - Pandruvada, Subramanya N.; Ebersole, Jeffrey L.; Huja, Sarandeep S.
Abstract: A crucial step in the pathogenesis of periodontal disease (PD) is activation of osteoclasts (OC) by numerous virulence factors produced by Porphyromonas gingivalis ( Pg ). To understand pathogenesis of PD and the role of specific adaptive immune responses, effects of antibodies on Pg ‐induced OC differentiation and function were investigated. Human peripheral blood‐derived monocytes were differentiated to OC in the presence or absence of: (a) Pg ; (b) antibodies to Pg ; and (c) antibody‐opsonized Pg . Findings suggest significant induction of osteoclastogenesis by Pg when compared to control cultures, whereas opsonization decreased osteoclastogenesis by 45%. Immune receptor gene expression profile in the presence of opsonized Pg showed marked upregulation of TLR1 (three‐fold) and TLR2 (twofold) along with FcγRIIB (two‐fold) and FcγRIII receptors (five‐fold), but not TLR4 and FcRγ receptors. Interestingly, blocking FcγRIIB, but not FcγRIII receptor, reversed the inhibitory effects of opsonized Pg suggesting a critical role played by FcγRIIB in osteoclastogenesis. Furthermore, opsonized Pg transformed OC precursors to a "macrophage phenotype" suggesting a bone protective role of the immune complexes in modulating osteoclastogenesis, probably by competing as an agonist for pattern recognition receptors, and inducing selective activation of FcγRs with simultaneous suppression of FcRγ which regulates bone resorptive process. Further defining effective antibody isotypes, avidity, and antigenic specificity could improve targets for eliciting protective immunity.